Systematic Review Of Spiritual Impact Of Recovery Stroke Outcome - Dwi Mulianda; Margiyati Margiyati; Chandra Bagus Ropyanto (International Journal Of Health Science, 2023)
Numerous functional impairments that stroke patients face lead to a decreased quality of life, powerlessness, and suicidal thoughts. Spirituality-based stroke recovery interventions may have mechanisms that aid in the healing process and can help create more thorough and efficient stroke rehabilitation programs. Methodology This study is a review that is systematic. The researchers used Google Scholar databases to look for data sources. The terms "stroke" and "spiritual OR other intervention" are employed, along with "and" recovery results. In the Google Scholar database, 980 journals were located. Just five of the articles overall satisfied the requirements for inclusion. Articles should discuss the effects of any kind of spiritual assistance on stroke sufferers' prognoses. bleeding and ischemic stroke of the older adult variety. Articles must employ RCT, qualitative, experimental, and mixed methods designs. The articles were published in full text and in the English language. Result Increased spirituality, holistic care, improved spiritual health, and higher self-efficacy in self-care were all impacted by the research. Restoring functional independence and faith did not correlate, according to a single study. Conclusion This review demonstrates how faith affects stroke survivors' ability to heal. It is suggested that programs for stroke care contain spiritual components.